THEORETICAL AND PRACTICAL PROBLEMS OF URBANIZATION - Kholmirzaev Nodirjon (Bright Mind Publishing, 2025)
The article deals with issues such as presidential decrees and resolutions, administrative territorial issues, command, paperwork, corruption, mistrust of management, familiarity, improper documentation, illegal construction, unemployment, quality education, quality medicine, integration of rural and urban relations.
Keywords: Administrative territorial issues, bureaucracy, red tape, corruption, mistrust of management, familiarity, uncleanness of documents, illegal construction.